Antiulcer Potential of Psidium guajava Seed Extract Supported by Metabolic Profiling and Molecular Docking - Nourhan Hisham Shady; Hend Samy Abdullah; Sherif A. Maher; Amgad Albohy; Mahmoud A. Elrehany; Fatma Alzahraa Mokhtar; Hesham Farouk Oraby; Ahmed M. Shawky; Usama Ramadan Abdelmohsen (Antioxidants, 2022)
One of the most severe human health problems is gastric ulceration. The main aim of our study is to explore the gastroprotective effect of the Psidium guajava seeds extract (PGE). Metabolic profiling based on LC-HRMS for the extract led to the dereplication of 23 compounds (1–23). We carried out a gastric ulcer model induced by indomethacin in male albino rats in vivo and the extract of PGE was investigated at a dose of 300 mg/kg in comparison to cimetidine (100 mg/kg). Furthermore, the assessment of gastric mucosal lesions and histopathology investigation of gastric tissue was done. It has been proved that Psidium guajava seeds significantly decreased the ulcer index and protected the mucosa from lesions. The antiulcer effect of Psidium guajava seed extract, which has the power of reducing the ensuing inflammatory reactions, can counteract the inflammation induced by indomethacin by the downregulation of relative genes expression (IL-1β, IL-6, and TNF-α). Moreover, PGE significantly downregulated the increased COX-2, TGF-β, and IGF-1 relative genes expression, confirming its beneficial effect in ulcer healing. Moreover, the possible PGE antioxidant potential was determined by in vitro assays using hydrogen peroxide and superoxide radical scavenging and revealed high antioxidant potential. Additionally, on the putatively annotated metabolites, an in silico study was conducted, which emphasized the extract’s antiulcer properties might be attributed to several sterols such as stigmasterol and campesterol. The present study provided evidence of Psidium guajava seeds considered as a potential natural gastroprotective agent.